Gender analyses on knowledge and awareness of COVID-19 on wearing face mask behaviour for self-protection among elderly Malaysians - Zainalaludin, Zumilah; Mat Din, Hazwan; Saidi, Norehan; Minhat, Halimatus Sakdiah; Raja Adnan, Raja Nurzatul Efah; Nor Akahbar, Siti Aisyah (Human Resource Management Academic Research Society, 2021)
This paper aimed to measure the variable that predicts the likelihood of female respondents to wear face mask. The data were collected (n=501) through online survey using Google Form. The set of questionnaire included the respondents’ background, knowledge about COVID-19, the awareness on COVID-19, and behaviour related to COVID-19 protection especially in wearing a face mask, washing hands, and social distance. Respondents in this study comprised the majority of females, Malay ethnic and from urban areas, at average age=65.55 years old. Majority (75.25%) reported that they are unemployed, married (78.24%), and had tertiary education (74.85%). Knowledge and awareness on COVID-19 significantly predict respondents to wear face mask. High knowledge predicts 19.194 times the likelihood of respondents to wear face mask, and high awareness predicts that less than 95.6% of respondents to wear face mask. Nevertheless, no variable predicts male respondents to wear face mask, and only high knowledge in COVID-19 predicts 41.340 times the likelihood of female respondents to wear a face mask. As conclusion, only high knowledge of COVID-19 predicts the behaviour of wearing face mask. Thus, effort should be focused on providing the public with good knowledge of COVID-19 to sustain good behaviour with regard to COVID-19 protection.